2014
DOI: 10.1186/s12870-014-0269-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of carotenoid accumulation in two goji (Lycium barbarum L. and L. ruthenicumMurr.) fruits

Abstract: BackgroundThe traditional Chinese medicinal plants Lycium barbarum L. and L. ruthenicum Murr. are valued for the abundance of bioactive carotenoids and anthocyanins in their fruits, respectively. However, the cellular and molecular mechanisms contributing to their species-specific bioactive profiles remain poorly understood.ResultsIn this study, the red fruit (RF) of L. barbarum was found to accumulate high levels of carotenoids (primarily zeaxanthin), while they were undetectable in the black fruit (BF) of L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 68 publications
4
41
0
Order By: Relevance
“…It is interesting to note that, due to the intense orange-red color of these C 30 apocarotenoids, the citrus CCD4 activity enhances fruit pigmentation, in contrast to the other CCD4s described so far whose activity is associated with color loss. In other species, such as bitter melon, goji berry, and tomato, the expression of at least one CCD4 gene has been reported in ripened fruits, but no relationship has been established with carotenoid content [148,155,163]. In potato tubers, compared with the yellow ones, CCD4 activity regulates coloration, as indicated by the elevated CCD4 expression in mature white-fleshed tubers [150].…”
Section: Plant Ccdsmentioning
confidence: 99%
“…It is interesting to note that, due to the intense orange-red color of these C 30 apocarotenoids, the citrus CCD4 activity enhances fruit pigmentation, in contrast to the other CCD4s described so far whose activity is associated with color loss. In other species, such as bitter melon, goji berry, and tomato, the expression of at least one CCD4 gene has been reported in ripened fruits, but no relationship has been established with carotenoid content [148,155,163]. In potato tubers, compared with the yellow ones, CCD4 activity regulates coloration, as indicated by the elevated CCD4 expression in mature white-fleshed tubers [150].…”
Section: Plant Ccdsmentioning
confidence: 99%
“…used Actin as a reference gene in fruits of two goji cultivars ( Lycium barbarum L. and L. ruthenicum Murr.) for the profiling of genes involved in carotenoid biosynthesis and metabolism13. However, our study demonstrated that LbActin7 exhibited moderately stable expression in some of the treatments in flowers and fruits, but introduced significant errors when normalizing the target gene expression level in leaves and fruits at specific developmental stages (Fig.…”
Section: Discussionmentioning
confidence: 77%
“…Unlike plants from the same Solanaceae family such as tobacco, tomato, pepper and potato, the whole genome data of Goji are still not available. Previously, Liu and co-workers13 used actin as a reference gene to analyze the expression pattern of genes involved in carotene synthesis in Goji. However, the validity of results is questionable due to the lack of systematic and scientific screening of reference genes.…”
mentioning
confidence: 99%
“…Recent research indicates that goji had a lot of biological activities, including antidiabetes [5], antiproliferative activity [4], preserving retinal function [6], and antioxidant activity [7,8]. A lot of research has focused on carotenoids [3] and polysaccharides [4,6]. However, phytochemicals [9,10], such as phenolic compounds [11], including phenolic acids and flavonoids in goji and their antioxidant activity have been less evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…natively growing in northwest part of China. Goji is a good source of fiber, protein, carotenoids [3], and polysaccharides [4]. Recent research indicates that goji had a lot of biological activities, including antidiabetes [5], antiproliferative activity [4], preserving retinal function [6], and antioxidant activity [7,8].…”
Section: Introductionmentioning
confidence: 99%